Gender Resistance in Women's Beauty in TikTok - Imelda, Reza Wani; Prayogo, Rangga Adi; Silvia, Novita; Th. Musa, Dahniar; Alamri, Annisa Rizqa (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2024)
Beauty is an important thing that is maintained by the majority of women. One way to maintain beauty is to use various beauty products. Apart from beauty according to the construction of various cultures, now there seems to be a generalization of beauty standards. This article was created to explain the form of rejection of beauty standards that become stereotypes on social media platforms. The method used in collecting data uses ethnographic methods, and literacy studies. The theory used is the theory of 'Social Reality' which was put forward by Peter L. Berger and Thomas Luckmann. So it can be concluded that gender resistance to women's beauty on tiktok shows that there is significant gender in the context of beauty on tiktok. Women use this platform to defy gender expectations and express themselves in ways that are more authentic and free from existing norms. They try to change the commonly accepted definition of beauty and show diversity in physical appearance and lifestyle.